CORRELATION BETWEEN CORONARY HEART DISEASE (CHD) AND PERIPHERAL ARTERY DISEASE (PAD) - Galih Pria Pambayun (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Peripheral Artery Disease (PAP) is a disease of the blood vessels. Peripheral Artery Disease (PAP) occurs due to the formation of atherosclerosis which causes the reduction of blood flow to the extremities. Peripheral arterial disease (PAP) is also common in patients with coronary heart disease (CHD) because in patients with coronary heart disease (PJK) has a pathophysiology of atherosclerosis similar to atherosclerosis occurring in peripheral artery disease (PAP). Aims: This study aims to determine the relationship between Coronary Heart Disease (CHD) with Peripheral Artery Disease (PAP) at Sultan Agung Islamic Hospital. Methods: The study was an analytic observational study with cross sectional design and was conducted at Sultan Agung Semarang Islamic Hospital in November-December 2014. Diagnosis of Peripheral Artery Disease (PAP) was known by using primary data that was by measuring Ankle Brachial Index (ABI). Results: The results showed that 42% of patients with Coronary Artery Disease (CHD) had Peripheral Artery Disease (PAP) and 10% of patients with Coronary Artery Disease (PAP) did not have Peripheral Artery Disease (PAP). Forty pecent of Non-Coronary Heart patients did not have Arterial Disease Peripheral (PAP), and 8% of patients with Non Coronary Heart Disease Peripheral Artery (PAP) Conclusion: This study showed that patient with Coronary Heart Disease (CHD) most likely will develop Peripheral Artery Disease (PAD).